Correction to: Antiobesity potential of Piperonal: promising modulation of body composition, lipid profiles and obesogenic marker expression in HFD-induced obese rats - Balaji Meriga (Nutrition & Metabolism, 2017)
Correction Following publication of the original article [1], the authors requested a correction to the name of one of the co-authors. The correct name and spelling is V.V. Sathibabu Uddandrao. The original article has been updated.